2022
DOI: 10.1111/1756-185x.14446
|View full text |Cite
|
Sign up to set email alerts
|

Medications impact different aspects of the quality of life of patients with systemic lupus erythematosus

Abstract: Purpose In this real‐world observational study, we analyzed the effects of different drugs on the quality of life (QoL) of patients with systemic lupus erythematosus (SLE). Method We identified patients in our prospective SLE Registry who received new medications. We measure QoL with MOS 36‐Item Short‐Form Health Survey (SF‐36), a generic health questionnaire, and SLEQOL, a disease‐specific instrument. We compared the patients' scores before and after initiation of treatment. Results We identified 259 episodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Although many pharmacological therapies for SLE exist, there is potential for both short- and long-term side effects ( 54–56 ), and a recent observational study showed that some pharmacological treatments yield better improvements in quality of life than others ( 57 ). Pharmacological therapies are typically targeted at reducing disease activity and preventing mortality; remission is not always possible ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although many pharmacological therapies for SLE exist, there is potential for both short- and long-term side effects ( 54–56 ), and a recent observational study showed that some pharmacological treatments yield better improvements in quality of life than others ( 57 ). Pharmacological therapies are typically targeted at reducing disease activity and preventing mortality; remission is not always possible ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SLE treatment protocols include the base of conventional synthetic DMARDs, the most important of these are hydroxychloroquine and glucocorticoid. Others include azathioprine, methotrexate, cyclosporine, mycophenolic acid analog, and cyclophosphamide in severe disease 1,11 . The biological agents include B‐cell depletion therapy and interferon targeting therapy, including rituximab, belimumab, and anifrolumab 12 .…”
Section: Current Therapies and Ongoing Research In Slementioning
confidence: 99%